Low Dietary Omega-6 to Omega-3 Fatty Acid Intake Ratio Enhances Adiponectin Level in Obesity - Helena Fabiani; Ninik Mudjihartini; Wiji Lestari (World Nutrition Journal, 2021)
Every year around the world, the prevalence of obesity is increasing. Obesity and its associated diseases have become some of the most pressing health problems in developed and developing countries. In its development, adipocytes dysfunction and chronic low-grade inflammation occur in obesity will stimulate diseases at higher risk including type 2 diabetes mellitus (T2DM), atherosclerosis, hypertension, and metabolic syndrome. Western diet and sedentary lifestyle are thought to have significantly contributed to the increase in obesity recently. Diet modification is a sound method to prevent obesity and its complications. Nevertheless, the concern lies in the ratio of omega-6 towards omega-3 fatty acidsÂ intake, which in its current state indicates an imparity. Omega-3 and omega-6 are two essential fatty acids that emerge as dominant factors in obesity through adiponectin. Adiponectin refers to a protein hormone conceived by adipocytes to prevent obesity and its subsequent complications by increasing insulin sensitivity, fatty acid oxidation, anti-inflammatory, and antiaterogenic. This study aims to determine the mechanism and the role of fatty acids in omega-6 towards those within omega-3 by using adiponectin as the indicator of advancement to obesity and its underlying diseases.